2021
DOI: 10.1177/15333175211027681
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Autonomic Exercise Improving Cognitive Function of Alzheimer’s Disease by Regulating lncRNA SNHG14

Abstract: This paper studied the influence of exercise on the cognitive ability of AD patients and elucidated potential mechanisms. The expression of SNHG14 was validated by qRT-PCR. The cognitive impairment of mice was examined by MWM Test. ELISA tests were applied to discover the influence of SNHG14 on inflammation. Overexpression of SNHG14 was found in AD patients and underexpression of SNHG14 was identified in these AD patients after exercise. In APP/PS1 double transgenic mice, SNHG14 reversed the protective impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The mechanism underlying exercise in AD has been explored by some authors. For example, the exercise meliorates MMSE and ADAS-Cog scores, and inhibits the raised expression of lncRNA SNHG14 [13]. In another investigation of AD patients, the levels of miR-129-5p were enhanced induced by physical exercise, and correlations were identified between miR-129-5p and ADAS-Cog and MMSE scores [17].…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism underlying exercise in AD has been explored by some authors. For example, the exercise meliorates MMSE and ADAS-Cog scores, and inhibits the raised expression of lncRNA SNHG14 [13]. In another investigation of AD patients, the levels of miR-129-5p were enhanced induced by physical exercise, and correlations were identified between miR-129-5p and ADAS-Cog and MMSE scores [17].…”
Section: Discussionmentioning
confidence: 98%
“…23 The researchers also found that in experimental mice with Alzheimer's disease, mice receiving exercise intervention could suppress inflammatory activity and improve their cognitive levels by reducing the level of lncRNA SNHG14. 24 Besides, Shi et al found that lncRNA SNHG14 activated the IL-1 receptor-associated kinase 4/nuclear factor-κB signaling pathway by binding to miR-93, which accelerated the inflammatory damage of septic induced AKI cells. 25 In this study, from the in vitro AGA cell model, it was noted that excessive lncRNA SNHG14 induced the inflammatory response of THP-1 cells, while silencing lncRNA SNHG14 significantly inhibited the production of IL-1β, IL-6, and TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al reported that lncRNA SNHG14 expression was increased in ischemic stroke, and that reducing lncRNA SNHG14 levels attenuated brain tissue damage and inflammation in a mouse model 23 . The researchers also found that in experimental mice with Alzheimer's disease, mice receiving exercise intervention could suppress inflammatory activity and improve their cognitive levels by reducing the level of lncRNA SNHG14 24 . Besides, Shi et al found that lncRNA SNHG14 activated the IL‐1 receptor‐associated kinase 4/nuclear factor‐κB signaling pathway by binding to miR‐93, which accelerated the inflammatory damage of septic induced AKI cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In this model, angiotensin analogs inhibit inflammation and prevent cognitive impairment by inhibiting SNHG14, thus restoring miR-223-3p function [ 74 ]. Exercise that improves cognition and reduces inflammation markers can also reduce SNG14 levels, in mice models and AD patients [ 75 ].…”
Section: Long Non-coding Rnas In Alzheimer’s Disease Related To Infla...mentioning
confidence: 99%